2014
DOI: 10.1371/journal.pone.0103685
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nasal Airway Homeostasis and Inflammation in Mice by SHP-1 and Th2/Th1 Signaling Pathways

Abstract: Allergic rhinitis is a chronic inflammatory disease orchestrated by Th2 lymphocytes. Src homology 2 domain-containing protein tyrosine phosphatase (SHP)-1 is known to be a negative regulator in the IL-4α/STAT-6 signaling pathway of the lung. However, the role of SHP-1 enzyme and its functional relationship with Th2 and Th1 cytokines are not known in the nasal airway. In this study, we aimed to study the nasal inflammation as a result of SHP-1 deficiency in viable motheaten (mev) mice and to investigate the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Further analysis of the lungs in mev mice reveals a Th2-like inflammatory response, including eosinophilia, increased Th2 cytokines IL-4, IL-5, and IL-13 but not IFN-g, and increased Stat6 phosphorylation [134]. This Th2 skewing was also seen in the upper airway and nasal mucosa [135]. mev mice that also lack Stat6 or IL-4 have significantly reduced lung inflammation.…”
Section: Mast Cells and Basophilsmentioning
confidence: 88%
“…Further analysis of the lungs in mev mice reveals a Th2-like inflammatory response, including eosinophilia, increased Th2 cytokines IL-4, IL-5, and IL-13 but not IFN-g, and increased Stat6 phosphorylation [134]. This Th2 skewing was also seen in the upper airway and nasal mucosa [135]. mev mice that also lack Stat6 or IL-4 have significantly reduced lung inflammation.…”
Section: Mast Cells and Basophilsmentioning
confidence: 88%
“…Consistent with previous findings, these data show here for the first time, reductions in goblet cell formation (as indicated by PAS staining) in RSV+ neonatal lungs treated with inhaled IFNγ (16 ng/g and 60 ng/g) when compared to untreated RSV+ pups. Mounting evidence continues to support the role of IFNγ as a regulator of mucus production [ 34 36 ]. Determining its precise mechanism in decreasing mucus production during neonatal RSV infection is an ongoing focus of research in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…IL-27 inhibits IFN-γ-induced autophagy by concomitant induction of the JAK/PI3K/Akt/mTOR cascade, in addition, Th2 cytokines IL-4 and IL-13 can also inhibit IFN-γ-induced autophagy [14, 81, 123]. Conversely, IFN-γ is considered as a regulator to Th2 responses, and deletion of IFN-γ gene strongly triggers Th2 cytokines secretion in inflammatory diseases [124]. Type III IFNs (IFN-λs) share some common characteristics and therapeutic benefits with type I IFNs, but the effects on cellular autophagy are different from type I IFNs.…”
Section: The Relationship Between Autophagy and Cytokinesmentioning
confidence: 99%
“…A study has indicated that IL-10 inhibits angiotensin II-induced pathological autophagy by activating PI3K/Akt/mTORC1 signaling and promoting Bcl2-Beclin1 interaction that could attenuate the anti-apoptosis effect; however, pharmacological or molecular inhibitors of Akt and mTORC1 signaling can weaken IL-10-inhibited Ang II-induced autophagy [137]. Furthermore, IL-4 and IL-13 signaling also activate PI3K signaling to activate mTORC1 in macrophage cells, and Th2 cytokines IL-4, IL-13 and IL-10 exert autophagy inhibition in most environments [124]. During monocytes–DCs differentiation and DCs survival, cytoprotective autophagy responses are essential for counteracting IL-10-triggered apoptosis, but IL-10 can strongly inhibit starvation-induced autophagy and decrease Bcl-2 levels, which indicates increased levels of Beclin-1, LC3, and mature autophagosomes and results in restricting DCs growth.…”
Section: The Relationship Between Autophagy and Cytokinesmentioning
confidence: 99%